(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is among the most important countries regarding ancient healing traditions. Its rich array of medicinal plants is used both in commerce and by local populations. However, unfortunately only a small percentage of these medicinal plants are cultivated. The plants years together are propagating by natural way with different means of reproduction and to some extent they are also cultivated for some or other value. The exploitation of such plant species to the extent of extinction made alarming situations worldwide to conserve them for sustainable use. The situation brought them to the list of red data book. Such plant species should be conserved in their natural home and should have been reproduced artificially by studying their intricate mechanism of reproduction in the niche of ecological conditions. Pollination is the transfer of pollen grains from the anther to the stigma. It is one of the most critical stages in the life cycle of flowering plants, involving a complex series of cell-cell interactions that constitute the pollen- pistil interaction. In this Article, we studied the concept of Medicinal Plants, their uses and Pollination in Angiosperms in detail.